Pubertal influences on neural activation during risky decision-making in youth with ADHD and disruptive behavior disorders. (April 2019) - Dir, Allyson L.; Hummer, Tom A.; Aalsma, Matthew C.; Hulvershorn, Leslie A.
Abstract: Objective: Risk-taking during adolescence is a leading cause of mortality; Neuroscience research examining pubertal effects on decision-making is needed to better inform interventions, particularly among youth with attention-deficit/hyperactivity (ADHD) and disruptive behavior disorders (DBD), who are particularly prone to risky decision-making. We examined effects of pubertal development on risky decision-making and neural activation during decision-making among youth with ADHD/DBDs. Method: Forty-six 11–12-year-olds (29.4% girls; 54.9% white; Tanner M(SD) = 2.08(1.32)) who met DSM-5 criteria for ADHD/DBD completed the Balloon Analog Risk Task (BART) during fMRI scanning. We examined effects of Tanner stage, sex, and age on risky decision-making (mean wager at which individuals stopped balloon inflation) and neural activation in the middle frontal gyrus and the ventral striatum during the choice and outcome phases of decision-making. Results: Those in earlier pubertal stages made riskier decisions during the BART compared to those in later Tanner stages (β=-0.62, p = .02). Later pubertal stage was associated with greater activation in the left middle frontal gyrus (β=0.61, p = .03) during the choice phase and in the right ventral striatum in response to rewards (β=0.59, p = .03). Conclusion: Youth with ADHD/DBD in later stages of puberty, regardless of age, show greater ventral striatal activation in response to rewards.